What Clinicians Should Know about Genetics - Vinall, Maria (MD Conference Express, 2008)
In the last year, there has been an explosion in the discovery of new genes that are related to autoimmunity. The sudden increase began with the discovery of a single nucleotide polymorphism in the gene PTPN22 that holds a 2-fold increased risk for a number of autoimmune disorders, including rheumatoid arthritis (RA). This article discusses the significant variations in risk alleles, sometimes based on ethnic groups, and how these variations confer significant differences in risk for RA diseases.